Railways as portals of globalisation: The case of the Portuguese mainland and colonial rail networks (1850–1915) - Pereira, Hugo Silveira (2018)
Railway construction in the Portuguese mainland began in the early 1850s and in the Portuguese colonies in the early 1880s. In both cases, railways sought the frontier and to attract transnational flows, motivated by the Saint-Simonian ideology and promise of promoting circulation, cross-border communications, and overall progress. However, these goals could be hampered by the development of the Nation-State and the conflicting agendas European nations had set for their overseas domains in Africa. In this paper, I will analyse the Portuguese mainland and colonial railways as portals of globalization. I will show how the conflict between globalization and nationalism was handled and how global flows fostered by railways were set, despite the opposition of the emerging Nation-States in Portugal and its European and colonial neighbours.